2018
DOI: 10.1111/ane.12918
|View full text |Cite
|
Sign up to set email alerts
|

Pseudobulbar affect as a negative prognostic indicator in amyotrophic lateral sclerosis

Abstract: These preliminary results underlie that the presence of PBA at entry negatively influences survival in a specific subgroup of patients with ALS characterized by less functional impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
(41 reference statements)
0
8
0
Order By: Relevance
“…It is not certain if prognostic factors affecting ALSFRS-R decline rate influence the survival. To date, there has been only one study describing a possible impact of EL on the ALS outcome [45]. It showed a slightly shorter survival of patients with EL, without reaching statistical significance (p=0.25).…”
Section: Discussionmentioning
confidence: 97%
“…It is not certain if prognostic factors affecting ALSFRS-R decline rate influence the survival. To date, there has been only one study describing a possible impact of EL on the ALS outcome [45]. It showed a slightly shorter survival of patients with EL, without reaching statistical significance (p=0.25).…”
Section: Discussionmentioning
confidence: 97%
“…We failed to observe a significant impact of PLC on survival in ALS patients in a multivariate Cox regression model analysis. A previous study found that the presence of PLC at recruitment can be a negative prognostic factor for survival in a very early stage of the disease, suggesting a short survival in a subgroup of patients with less functional impairment ( 11 ). However, this study lacked the neuropsychological evaluation for the relationship between PLC and other symptoms such as frontal dysfunction or cognitive impairment in general.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive dysfunction is a non-motor symptom in ALS with the severity of cognitive decline ranging from mild cognitive impairment to ALS frontotemporal dementia involving executive and non-executive domains ( 10 ). The relationship between PLC and cognitive impairment is controversial in ALS ( 11 ). Further studies with a larger sample size are required to explore the individualized experiences of PLC in ALS.…”
Section: Introductionmentioning
confidence: 99%
“…34,87,88 Cognitive impairment, which has been identified in as many as 51% of PALS, may include frontotemporal dementia, cognitivebehavioral impairment, and nonexecutive findings. 89,90 As cognitive screening instruments validated for bulbar ALS are urgently needed…”
Section: Extrabulbar Itemsmentioning
confidence: 99%